Organochlorine and organophosphoric insecticides, herbicides and heavy metals residue in industrial wastewaters in Cyprus - Fatta-Kassinos, Despo; Canna-Michaelidou, Stella; Michael, C.; Demetriou Georgiou, E.; Christodoulidou, Maro; Achilleos, A.; Vasquez Christodoulou, Marlen (My University, 2007)
Most industries in Cyprus possess permits either for disposal at central wastewater treatment plants (the treated effluent of which is reused or disposed into the sea), or discharge on soil, or reuse either for irrigation or groundwater recharge or discharge into the sea. A preliminary investigation undertaken by the University of Cyprus in regards to dangerous substances was the first step towards establishing a new licensing and monitoring system. Liquid-liquid extraction was used for the extraction of the selected pesticides from wastewaters. Gas chromatography with two different detection methods (ECD and FTD) was applied for the determination of 17 pesticides (12 organochlorine insecticides, 3 organophosphoric insecticides and 2 herbicides). In addition ICP and a mercury evaporation unit were used to determine the concentrations of heavy metals in the samples. The results revealed the presence of several priority substances in wastewaters, in most cases at concentrations well below the regulatory limits. Non-compliance was observed for a limited number of metals. Sixteen out of 17 organic substances that were monitored for 1-year period time were traced in different wastewater streams. What was found out is that there is a need to expand the analytical determinations and the monitoring to more wastewater streams and more priority substances, in order to safeguard the water resources in Cyprus.
Keywords: Organochlorine; Organophosphoric insecticides; Herbicides; Industrial wastewaters; Cyprus